Working with street children : gender dimension of intervention and approaches. Case study of outreach program in Dar es Salaam Tanzania - Heinoja, Wende (2011)
The aim of this thesis was to study the concept of gender in understanding, and working with street children. Gender is arguably one of the important issues in understanding street children. Studying gender in intervention is linked to effective practices of assisting street children because gender focus on differences among different groups of girls and boys in the street. Gender in this research has been conceptualised as a status that is being continually produced and reproduced during social interaction. The thesis is divided in two main parts. The first part reviews the available literature on gender and street children. The second part is empirical case study of outreach activities of DSCT, a non governmental organisations working with street children in Dar es Salaam Tanzania. The empirical part is qualitative study. Data were collected through participant observation, semi structured interview, and review of documents. Review of literature showed that majority of street children are boys. There are small but significant number of girls living and working in the streets. Girls and boys in the streets have different opportunities to make a living, constraints, and coping strategies. The interventions often have not considered gender differentiated needs and circumstances of street children. Often interventions of street children reproduce gender through their approaches which have gendered assumption or through provision of skills based on gender stereotype. The findings from DSCT first revealed the gendered use of space. Secondly, it showed how intervention reproduces gender through concentrating their activities to areas where only older street boys are found. Thus girls and young boys who spend their times in the back streets of city centre remained invisible and with limited opportunities.